Taxa de gestação de femeas Nelore confinadas, submetidas á inseminação artificial em tempo fixo - Lucas Fernando Ventura Ferreira (2017)
We aimed with the present study to evaluate the effect of one or two PGF2 treatments in a protocol for ovulation induction on pregnancy rates in Nelore females kept in confinement inseminated at fixed time (TAI). A retrospective analysis was performed in data obtained from a commercial farm. Data from 5,650 inseminations were used, and the statistical analyses were done considering only the lots with a uniform distribution in each category. Therefore, a total of 523 heifers, 559 non-lactating cows, and 2,279 lactating cows were used. All animals from the three categories were synchronized by an estradiol and progesterone (P4) based protocol. On Day 0, all animals received an intravaginal P4 device (CiDR®, Zoetis) along with an intramuscular treatment of 2mg estradiol benzoate (Gonadiol®, MSD Saúde Animal). On Day 7, all animals received a reduced dose of de dinoprost tromethamine (12,5 mg; Lutalyze® - Zoetis). The P4 device was removed and 0,6 mg of estradiol cypionate (ECP®, Zoetis) was administered intramuscularly on Day 9. In addition, 300 UI of eCG (Novormon® - MSD Saúde Animal) was injected only in the lactating cows. Within each category, the same ovulation synchronization protocol was used, with the single difference of the number of PGF2 analogue doses, resulting in formation of the following two groups: administration of a single reduced dose of PGF2 analogue on Day 7 (D7), or two reduced doses on Days 7 and 9 (D7/9). Therefore, six experimental groups were formed: heifers (NOV-D7 and NOV-D7/9), non-lactating cows (SOL-D7 and SOL-D7/9) and lactating cows (PAR-D7 and PAR-D7/9). The animals from NOV-D7/9, SOL-D7/9 and PAR-D7/9 groups received a second PGF2 treatment of Day 9. On Day 11, all animals were artificial inseminated at fixed time with semen from proven bulls. The binomial variable pregnancy rate was evaluated by logistic regression, using the PROC GLIMMIX from SAS software. The independent variables were included in the initial model and then removed according to the Walds criterion (P>0.2). The pregnancy rate did not differ (P>0.05) between the heifers in the NOV-D7 (39.1%, 110/277) and NOV-D7/9 (41.63%, 102/245) groups. Similarly, a significant difference was not observed between the cows from PAR-D7 (51.65%, 594/1,150) and PAR-D7/9 (51.38%, 580/1,129) groups. However, the pregnancy rate was greater (P<0.05) in the non-lactating cows from SOL-D7/9 group (41.7%, 105/299) than from SOL-D7 group (35.12%, 108/259). Additionally, a lot effect on pregnancy rate was observed in heifers and lactating cows, and this effect in lactating cows may be caused by the lower pregnancy rate in the lots of primiparous cows. In conclusion, the administration of two doses of 12.5 mg of dinoprost tromethamine is need for ovulation synchronization protocols in non-lacatating Nelore cows, aiming to improve pregnancy rates.